2003
DOI: 10.1046/j.1537-2995.2003.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Serologic analysis of three cases of neonatal alloimmune thrombocytopenia associated with HLA antibodies

Abstract: Transplacental passage of maternal HLA antibodies was observed in the three neonates cited in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…In humans, MHC class I alloantibodies in individual cases of fetal/neonatal alloimmune thrombocytopenia (FNAIT) have been reported a number of times during the past decades (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In addition to thrombocytopenia, the presence of an associated neutropenia is noticed in a few cases (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, MHC class I alloantibodies in individual cases of fetal/neonatal alloimmune thrombocytopenia (FNAIT) have been reported a number of times during the past decades (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In addition to thrombocytopenia, the presence of an associated neutropenia is noticed in a few cases (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…However, limited cases of FNAIT associated with HLA class I antibodies have been described. 11 In PTR cases, platelet specific antibodies against HPAs were detected in 4/74 cases only (5%). Anti-HPA2b (n = 1), anti-HPA-5a (n = 1), anti-HPA-5b (n = 2), anti-HPA-15b (n = 3) could also be identified.…”
Section: Resultsmentioning
confidence: 94%
“…Saito et al [2] provided serological analysis from three cases with assumed FNAITP in association with HLA antibodies. One offspring with low weight had severe respiratory distress and low Apgar scores.…”
Section: Reports On Hla Class I Incompatibilities and Fnaitp Since 2006mentioning
confidence: 99%
“…After carefully discussing the pros and cons, the author concluded that evidence that HLA antibodies may induce FNAITP is rather weak. Since this publication only three new papers have been dealing with neonatal thrombocytopenia which might be due to maternal alloantibodies with HLA class I specificity [2][3][4]. This review focuses on reports and data dealing with an association between an alloimmunization against HLA class I antigens and fetal/neonatal alloimmune thrombocytopenia (FNAITP) that have been published since 2000.…”
Section: Introductionmentioning
confidence: 99%